Living with otosclerosis: disease-specific health-related quality-of-life measurement in patients undergoing stapes surgery - Lailach, Susen; Baumann, Ingo; Walter, Hannah; Praetorius, Mark (European archives of oto-rhino-laryngology and head & neck, 2018)
Introduction: Otosclerosis is associated with hearing disability, leading to communication deficits and social and psychological restrictions. The objective of our study was to analyze disease-specific health-related quality of life (HRQOL) after stapes surgery and compare the outcome of HRQOL with audiometric parameters. Subjects and Methods: Our clinical case study was conducted at two tertiary referral centers. All the 37 patients who had undergone stapes surgery were analyzed clinically and by audiometric testing (pure tone and speech audiometry) in the pre- and postoperative settings. Disease-specific HRQOL was assessed by the validated Stapesplasty Outcome Test 25 (SPOT-25) pre- and postoperatively. The subjective hearing disability was evaluated by the hearing handicap inventory for adults (HHIA). The postinterventional benefit was measured by the Glasgow Benefit Inventory (GBI). Results: Disease-specific HRQOL improved significantly after stapes surgery in all scales of the SPOT-25. Postoperatively, the total score and the subscore “hearing function” correlated well with the audiometric data. The subscores “tinnitus”, “social restrictions”, and “mental condition” did not show significant association with audiometric parameters. The comparison of pre- and postoperative HHIA offered a significant improvement in the hearing disability. The scores of the HHIA correlated very well with the audiometric data. The GBI showed a postoperative benefit for each individual patient. Conclusion: Stapes surgery leads to a significant improvement in the hearing handicap and of disease-specific HRQOL. The audiometric parameters were shown as not being a sufficient indicator of social and mental well-being. HRQOL outcome measuring instruments should be used routinely in clinical practice to provide an individualized postoperative assessment.
First online: 07 November 2017
Gesehen am 25.10.2018